Studi Experimental Kinerja Mesin Pencacah Kertas Kapasitas 50 kg/Jam - Fauzi, Alfian; Sinaga, Andriansyah; Fadhillah, Yusuf; Hermanto, Tino (CV. IRA PUBLISHING, 2024)
The experimental study testing of the performance of a paper chopping machine with a capacity of 50 kg/hour in this research was motivated by the researcher's desire to test the performance of a paper chopper machine with a capacity of 50 kg/hour to find out the results of shredding paper and the capacity limits that can be used to chop paper based on the machine's capabilities. which will be built. This machine was built to reduce existing paper waste which will later be recycled into new paper products. The method used in this test is using an experimental method where the machine that will be used will chop each piece of paper with a shredded paper width of 10mm which will be inserted into the paper chopping machine. From the results obtained, the paper shredding machine was only able to produce 37.8% of the 50 kg/hour of shredded paper. The shredding results produced by the shredding machine did not contain any uncut defects or slanted cut defects produced by the paper shredding machine with a machine production capacity of only 19kg/hour. The maintenance used on paper shredding machines is preventive maintenance.